Determinants of app stores continuance behavior: a PLS path modelling approach - Rezaei, Sajad (Routledge, 2016)
Prior research has mostly examined the satisfaction, intention, and behavior of users toward technology and systems in general, and little research has been dedicated to understanding apps commerce and app stores. Drawing upon the extended model of IT continuance and theory of information overload as a theoretical foundation, the aim of this study is to examine consumer satisfaction, continuous intention, and behavior toward apps shopping. A total of 347 valid questionnaires were collected from experienced consumers with app stores to statistically test the theoretical model using the partial least squares path modelling approach, a structural equation modelling technique. The results show that apps self-efficacy, post-usage usefulness, disconfirmation, facilitating conditions, perceived information overload, apps satisfaction, and apps continuance intention can be used to predict and explain 75.7% of variance in consumer’s continuance behavior in using app stores. The negative and positive causal relationship between constructs, managerial implications, and limitations are discussed.